Analisis Optimasi Round Trip Time (RTT) pada Jaringan Transmission Control Protocol (TCP) New Reno - Harry Idwan; Ihsanuddin Ihsanuddin (KITA Institute, 2020)
The research objective is to simulate and analyze existing algorithms developed previously using the NS-3 application, which affects the measurement of RTT, cwnd, and throughput, and to evaluate the performance of TCP New Reno based on topology and research parameters so that it is obtained specifically how to optimize RTT and throughput on wireless networks. at the Banda Aceh City coffee shop. The research method simulates and analyzes the development of the TCP New Reno algorithm on wireless network coding so that the results can be applied directly. The approach describes a variety of steps or techniques based on a certain distance in increasing throughput, controlling the congestion window (cwnd) and reducing RTO. The results of the study concluded that the use of the TCP New Reno algorithm on a wireless network for multi-hop ad-hoc topology (5 nodes) produced better values than single-hop (2 nodes). The TCP New Reno algorithm has a retransmit phase (at flow-1 and flow-2) which indicates that the slow start phase again starts, cwnd will effectively double (slowly add data) the size of the windows RTT (time) thereby reducing the loss of data packets. In general, strategies and techniques based on distance (6 m and 3 m) in achieving RTT optimization, the TCP New Reno's network strategy of 3 m is a good technique, especially in multi-hop.